Favourable response to ketogenic dietary therapies: undiagnosed glucose 1 transporter deficiency syndrome is only one factor. (23rd April 2015) - Schoeler, Natasha E; Cross, Judith Helen; Drury, Suzanne; Lench, Nicholas; McMahon, Jacinta M; MacKay, Mark T; Scheffer, Ingrid E; Sander, Josemir W; Sisodiya, Sanjay M
<x xml:space="preserve">Abstract</x> Aim We aimed to determine whether response to ketogenic dietary therapies (KDT) was due to undiagnosed glucose transporter type 1 deficiency syndrome (GLUT1‐DS). Method Targeted resequencing of the SLC2A1 gene was completed in individuals without previously known GLUT1‐DS who received KDT for their epilepsy. Hospital records were used to obtain demographic and clinical data. Response to KDT at various follow‐up points was defined as seizure reduction of at least 50%. Seizure freedom achieved at any follow‐up point was also documented. Fisher's exact and gene‐burden association tests were conducted using the PLINK/SEQ open‐source genetics library. Results Of the 246 participants, one was shown to have a novel variant in SLC2A1 that was predicted to be deleterious. This individual was seizure‐free on KDT. Rates of seizure freedom in cases without GLUT1‐DS were below 8% at each follow‐up point. Two cases without SLC2A1 mutations were seizure‐free at every follow‐up point recorded. No significant results were obtained from Fisher's exact or gene‐burden association tests. Interpretation A favourable response to KDT is not solely explained by mutations in SLC2A1. Other genetic factors should be sought to identify those who are most likely to benefit from dietary treatment for epilepsy, particularly those who may achieve seizure freedom.